Participatory Timeline in Tunisia: National Workshop Report on Actor Perspectives on Behavioral Drivers, Agency, and Behaviour Change in Agroecological Transformation - Alary, Veronique; Frija, Aymen; Lestrelin, Guillaume; Braiki, Houssem; Hamrouni, Dhia; Idoudi, Zied; Mannai, Amal; M'hamed, Hatem Cheikh (International Center for Agricultural Research in the Dry Areas, 2023)
In 2022, the OneCGIAR, in collaboration with national and international partners, launched an initiative on agroecology across seven countries, including Tunisia. The initiative comprises five components focused on creating collaborative 'living landscapes,' implementing evidence-based agroecological assessments, developing inclusive business models, strengthening policy frameworks, and understanding behavior change. Within the initiative's fifth component, a plan was proposed to leverage past experiences and global research to identify transformative behavioral changes supporting agroecological transitions in Tunisia. A desk review, including an inventory, quick review of initiatives, and stakeholder interviews during a July 2023 workshop, aimed to revise a chronological timeline of key events influencing agroecological transformation in Tunisia over the past 20 years. The workshop sought to assess how these events impacted agency, behavior change, and representation across different actors in the food system. The ultimate objective is to establish a baseline for agency and behavior change across genders, ages, and groups, informing indicators to monitor changes during and beyond the initiative.